The Role of Matrix Metalloproteinases (MMP-2 and MMP-9) in Ageing and Longevity: Focus on Sicilian Long-Living Individuals (LLIs). (5th May 2020) - Cancemi, Patrizia; Aiello, Anna; Accardi, Giulia; Caldarella, Rosalia; Candore, Giuseppina; Caruso, Calogero; Ciaccio, Marcello; Cristaldi, Laura; Di Gaudio, Francesca; Siino, Valentina; Vasto, Sonya
Abstract : Extracellular matrix metalloproteinases (MMPs) are a group of proteins that activate substrates by enzymatic cleavage and, on the basis of their activities, have been demonstrated to play a role in ageing. Thus, in order to gain insight into the pathophysiology of ageing and to identify new markers of longevity, we analysed the activity levels of MMP-2 and MMP-9 in association with some relevant haematochemical parameters in a Sicilian population, including long-living individuals (LLIs, ≥95 years old). A cohort of 154 healthy subjects (72 men and 82 women) of different ages (age range 20-112) was recruited. The cohort was divided into five subgroups: the first group with subjects less than 40 years old, the second group ranging from 40 to 64 years old, the third group ranging from 65 to 89 years old, the fourth group ranging from 90 to 94 years old, and the fifth group with subjects more than 95 years old. A relationship was observed between LLIs and MMP-2, but not between LLIs and MMP-9. However, in the LLI group, MMP-2 and MMP-9 values were significantly correlated. Furthermore, in LLIs, we found a positive correlation of MMP-2 with the antioxidant catabolite uric acid and a negative correlation with the inflammatory marker C-reactive protein. Finally, in LLIs MMP-9 values correlated directly both with cholesterol and with low-density lipoproteins. On the whole, our data suggest that the observed increase of MMP-2 in LLIs might play a positive role in the attainment of longevity. This is the first study that shows that serum activity of MMP-2 is increased in LLIs as compared to younger subjects. As far as we are concerned, it is difficult to make wide-ranging conclusions/assumptions based on these observations in view of the relatively small sample size of LLIs. However, this is an important starting point. Larger-scale future studies will be required to clarify these findings including the link with other systemic inflammatory and antioxidant markers.